О компонентах словообразовательного значения и их соотношений в дериватах различных типов и частей речи - Англицкас, Вацловас (Kalbotyra, 1987)
The study of word building in different languages shows that derivational meaning is not an elementary formation but a complex one. Usually it reflects the categorical meaning of derivatives, generalized meaning of underlying stems and the type of correlation between these two components. In transpositional and modificational derivatives the correlative component is omitted while in the semantic derivation of adjectives and verbs a special stress is laid on it. The derivational meaning of nouns mainly emphasizes the semantic class to which derivatives belong, the correlational component being not specified.